2014
DOI: 10.5296/jet.v2i1.6577
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationship Between Factors That Contribute to Interactive Engagement and Academic Performance

Abstract: In an educational context, technology can prompt interactive engagement only when it is used in conjunction with interactive engagement methods. This study, therefore, examines the relationships between factors that contribute to higher levels of interactive engagement and performance, such as interactive engagement methods, technology, intrinsic motivation and deep learning. Five hundred and twenty-six (526) higher education students participated in this study. With structural equation modelling, the authors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Research has shown that science teaching can be learned from formal sources and at the same time it can enhance the learning quality of learners through teachers who plan their lessons using informal sources such as written, visual media, television programs, animations, simulations, video-films. Therefore, audiovisual tools and equipment are effective in science teaching (Diogo, António and Nilza, 2011;Tlhoaele, Hofman, Winnips and Beetsma, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that science teaching can be learned from formal sources and at the same time it can enhance the learning quality of learners through teachers who plan their lessons using informal sources such as written, visual media, television programs, animations, simulations, video-films. Therefore, audiovisual tools and equipment are effective in science teaching (Diogo, António and Nilza, 2011;Tlhoaele, Hofman, Winnips and Beetsma, 2015).…”
Section: Introductionmentioning
confidence: 99%